Susceptibility of Candida albicans to common and novel antifungal drugs, and relationship between the mating type locus and resistance, in Lebanese hospital isolates - Khalaf, Roy A. (2009)
The incidence of antifungal resistance is on the increase worldwide and novel drugs are constantly being developed to counter this trend. One hundred and sixteen clinical isolates of Candida albicans were collected from Lebanese hospitals in order to first determine the degree of resistance of Lebanese isolates to four common azoles: fluconazole (FL), itraconazole (IT), ketoconazole (KE), and voriconazole (VO), in addition to amphotericin B (AP) and caspofungin (CS) through the Epsilometer test method and second, determine any relationship between the allelic compositions of the mating type loci (MTLa, MTL α, MTLa/α) with drug resistance. Results showed that resistance, among C. albicans isolates, was the highest with 12% for IT, followed by 7.7% for VO, 6% for KE, 5% for FL, 1.7% for AP and 0% for CS. Three isolates (2.6%) were resistant to all azoles tested, including one that was resistant to all drugs used except CS. Eleven isolates were homozygous at the MTL locus (9.5%), five of which (45%) were resistant to at least one antifungal drug whereas 14 of the 105 heterozygous strains (13%) exhibited similar resistance (P = 0.02), indicating a strong correlation between MTL locus homozygosity and resistance.